Size control of gas phase grown silicon nanoparticles by varying the plasma OFF time in silane pulsed plasma. Issue 1803 (18th May 2015) - Mohan, A.; Poulios, I.; Schropp, R.E.I.; Rath, J.K.
ABSTRACT: Silicon nanoparticles are synthesized by very high frequency Plasma Enhanced Chemical Vapor Deposition (vhf-PECVD) in the gas phase. Pulsed plasmas are used to obtain particles with a narrow size distribution. The role of plasma OFF times is studied to tailor the size of the silicon nanoparticles. Various plasma OFF times are chosen, both longer- and shorter -than the residence time of the gases in the discharge. Time resolved optical emission spectroscopy (TROES) studies provide additional information about the growth precursor dynamics during plasma modulation. The size and the size distribution studies of the particles are done with transmission electron microscopy (TEM). These studies reveal that a plasma OFF time longer than the residence time is favorable for the formation of quantum sized silicon particles.